ANALISIS KEPUASAN PELANGGAN SPG PRO MELALUI CEI PADA PENANGANAN GROUP EVENT SHERATON BALI KUTA RESORT - Ni Ketut Narti; Luh Made Wijayati; I Wayan Putrana; Ni Putu Ika Pratami Sukarsa (Forum Manajemen, 2019)
The development of tourism, especially in the MICE sector in Bali is growing rapidly. That’s what makes most hotel business in Bali provide the best service for guests who come with business purpose. As well as Sheraton Bali Kuta Resort that provides special services for handling events and customers who hold events for themselves or others who are referred to as onsite contact. Starwood which is the owner company of Sheraton strengthen the communication with the customer in handling event through loyalty program for someone called as onsite contact this is SPG Pro where this program have interesting advantages for its member. This is an example of how Sheraton Bali Kuta Resort is very concerned about customer satisfaction especially SPG Pro customers. Through a survey of CEI (Customer Experience Index) of Sheraton Bali Kuta Resort, renew the quality of its services so that it matches the expectations of every customer.This study aims to find out how customer satisfaction SPG Pro in handling events at Sheraton Bali Kuta Resort through servei CEI. Of the 90 respondents, researchers used 50 samples that have passed the CEI survey. From result of sample which is processed by CSI analysis technique (Customer Satisfaction Index) it is known that SPG Pro customer is satisfied with amount of satisfaction equal to 77,43% and from 5 dimension of service quality, assurance is dimension which has highest score in relation between expectation and service quality.